The Relationship Between Diversification Strategy And Organizational Performance: A Research Intented For Comparing Belgium And Turkey - YİĞİT, İHSAN (ELSEVIER SCIENCE BV, 2013)
The aim of this study is to determine whether there is a significant difference between types of diversification and performance values comparing Turkey and Belgium. Diversification strategy and organizational performance relationship seems to differ across developed and developing countries. The data from 2007-2011 of 114 business groups in Belgium and 118 business groups in Turkey were analyzed. ROA and ROS for organizational performance and Rumelt's measure for diversification were used. According to the results, when organizational performance values are high for single businesses, dominant businesses and unrelated diversification in Belgium, organizational performance is high for dominant businesses in Turkey.
Keywords: Diversification Strategy; Organizational Performance; Developing Country; Developed Country; RESOURCE-BASED VIEW; CORPORATE DIVERSIFICATION; ECONOMIC-PERFORMANCE; INTERNATIONAL DIVERSIFICATION; FIRM PERFORMANCE; EMERGING MARKETS; BUSINESS GROUPS; PROFITABILITY; DIVERSITY; PRODUCT